The Association Between Placental Residual Blood Volume and Two Placental Transfusion Methods After Delivery at Term - Hung, Tai-Ho; Chuang, Ya-Chun; Huang, Lulu (Frontiers in Pediatrics, 2021)
Background: Despite reports of the beneficial effects, such as increasing hemoglobin level and iron store in the neonatal period, of delayed cord clamping or umbilical cord milking after delivery in healthy term-born infants, the duration of delayed clamping or rounds of milking in most previous reports were determined arbitrarily and varied widely across different studies. Methods: We prospectively recruited 80 women with normal singleton pregnancies at 38–40 weeks’ gestation. Participants were classified according to the mode of delivery and randomly assigned to either collecting blood from the placenta by umbilical cord drainage (CD) or cord milking (CM), with the placenta left in the uterus. The volume of blood collected, the duration of CD, and the number of rounds of CM were recorded. Results: Collected placental residual blood volume positively correlated with birth weight, placental weight, and length of the cord. When 80% of the total placental residual blood volume collected was set as the threshold, more than 80% of women who delivered vaginally reached this level within 60 s of CD or seven repetitions of CM. This amount of blood could be obtained within 120 s of CD or after seven repetitions of CM in more than 80% of women who underwent cesarean delivery. Conclusion: In most women, regardless of birth weight and placental weight, more than 80% of placental residual blood volume could be collected by CD within 60 s after vaginal delivery, 120 s after cesarean delivery, and seven repetitions of CM in both vaginal and cesarean deliveries.